Primary health care nursing students' knowledge of and attitude towards the provision of preconception care in KwaZulu-Natal - Winifred C. Ukoha; Makhosi Dube (AOSIS, 2019)
Background: Sub-Saharan African countries have been the worst affected by the high incidence of maternal and child mortality rates and HIV/AIDS (human immunodeficiency virus/acquired immunodeficiency syndrome) pandemic. Preventive care is the area that requires serious attention as a lot of maternal and child morbidity and mortality can be averted through rendering comprehensive care to women of child-bearing age. Preconception care (PCC) is recognised as an important factor in improving pregnancy outcome; yet, most primary health care (PHC) nurses lack the necessary resources to render PCC. Aim: To describe the PHC nursing student's knowledge of and attitude towards the provision of PCC. Setting: Higher Education Institution that offers PHC programme at six different sites to nurses working in the PHC clinics in the province. Methods: A quantitative, non-experimental, descriptive study design was used. The total population from three sites selected, based on their geographical location were all invited to participate in the study. Questionnaire was used to collect data which was subsequently analysed using the Statistical Package for Social Sciences (SPSS) version 24. Results: The response rate was approximately 85% (n = 138). The respondents have practised in the PHC clinic for more than 1 year. Study centre, age and area of employment were found to be predictors of knowledge, but no direct association was found between the demographic factor and attitude. Furthermore, a significant difference was found between knowledge and age, and between the area of employment and attitude. Conclusion: PHC nursing students were knowledgeable and had a favourable attitude towards PCC, but the absence of PCC resources in many practices has hindered them to a greater extent. It is recommended that for proper implementation of PCC to occur, health care workers should be provided with the necessary resources.